Food reserve composition in sago palm (Metroxylon sagu Rottb.) and influence of cluster age on survivability at the nursery stage - Howell, P. S.; Abdullah, Nur Ashikin Psyquay; Busri, Noraini; Bulan, Petrus; Jiwan, Make; Abdullah, Z. C.; Haruna, Ahmed Osumanu (2015)
Sago palm (Metroxylon sagu Rottb.) can be propagated by suckers which are normally nursed either using rafting or poly-bag system for at least three to four months before planting them in the field. With the establishment of sago plantation in Sarawak, suckers were harvested at rapid rate to fulfil the high demand for planting material. All available suckers were harvested regardless maturity and this resulting in high mortality rate during nursery stage experienced by the plantation. The objectives of the study were to determine the importance of food reserve in the rhizome and sago sucker maturity which influence the sucker survivability during nursery stage. Sucker survivability was recorded from the observation and monitoring nursed suckers using poly-bag system for six months. Sucker’s crude fibre, sugar and starch content were determined using Maynard procedure, Anthrone and Somogyi-Nelson method respectively. The result showed that sucker derived from mature sago clusters have higher survival rate (82.5%) than those from immature sago cluster (45%) during nursery stage. The moisture, crude fibre, starch and sugar contents in the fibrous upper part of both suckers were statistically similar, however significantly different percentage of moisture, crude fibre, starch and sugar content were observed in the rhizome of sucker from both types. High starch (29.21%) and sugar (4.38%) with low moisture (74.62%) and crude fibre (9.20%) in the rhizome of matured sucker indicate more food reserve and this enabled the sucker to survive when separated from the mother palm compared to sucker derived from immature sago clusters. Results showed that rhizome is one of the vital parts for survivability where food reserve was stored. Food reserve is also essential for the development of new roots and leaves to enable these parts to synthesize energy through the absorption of nutrients and photosynthesis activities. The findings of this study suggest that sucker from mature sago clusters can be used to produce planting material especially due to their high survival rate during nursery stage.